Precision Negative Inotropy: The Rise of Cardiac Myosin Inhibitors in HCM - Skibicka, Katarzyna; Skibicki, Tomasz; Wesołowska, Weronika; Bujak, Robert (Journal of Education, Health and Sport, 2025)
Background: Hypertrophic cardiomyopathy (HCM) is the most common heritable cardiomyopathy, marked by left-ventricular hypertrophy, dynamic outflow obstruction in many patients, diastolic dysfunction, and elevated risks of atrial fibrillation and heart failure. Conventional drugs improve symptoms but do not directly address sarcomeric hypercontractility. Cardiac myosin inhibitors (CMIs) attenuate excessive cross-bridge cycling via stabilization of autoinhibited/super-relaxed myosin states. Objective: To compare aficamten and mavacamten across mechanism, pharmacology, efficacy, safety, drug-drug interactions, and monitoring, highlighting MAPLE-HCM (aficamten vs metoprolol in obstructive HCM) and ODYSSEY-HCM (mavacamten vs placebo in nonobstructive HCM). Results: In obstructive HCM, CMIs improve gradients and functional capacity in randomized trials; MAPLE-HCM showed aficamten superiority over metoprolol for peak VO₂ and multiple secondary endpoints at 24 weeks. In nonobstructive HCM, ODYSSEY-HCM was neutral on its dual primary endpoints (peak VO₂, KCCQ-CSS) at 48 weeks, with more LVEF < 50% on mavacamten that typically resolved with interruption. Pharmacology and operations differ: aficamten’s shorter half-life and linear PK may enable tighter titration, whereas mavacamten requires REMS-guided monitoring and careful DDI management. Conclusions: For symptomatic obstructive HCM, CMIs represent mechanism-directed therapy; aficamten and mavacamten both have robust placebo-controlled evidence, and MAPLE-HCM positions aficamten as a plausible first-line option in appropriate patients. In nonobstructive HCM, routine CMI use is not supported by current randomized evidence. Long-term remodeling, arrhythmia outcomes, and phenotype-guided selection remain priorities.